PERLINDUNGAN HUKUM ANAK TERLANTAR: : Kajian Prespektif Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Rudy Catur Rohman Kusmayadi; Musleh (LP3M IAI Al-Qolam, 2022)
Abandoned children are children who do not get the same rights as children. their families and relatives are not able to carry out their obligations so that the needs of children's rights are not met. As stated in Law no. 35 of 2014 concerning child protection, which reads;